Analisa Strategi Generasi Sandwich dan Dampaknya terhadap Gaya Hidup Chidfree - Siti Nurjanah; Hermanto, Agus; Rimanto, Rimanto; Sulastri, Sulastri; Habib Ismail; Haikal (Bulletin of Community Engagement, 2024)
The sandwich generation often experiences ambiguity in determining their survival in the household, because this generation often experiences a mental burden on themselves because of the responsibilities they have to carry out. The problem is what impact will the sandwich generation have on the childfree lifestyle? The aim of this research is to see the childfree lifestyle that is popular with society today, and to what extent the sandwich generation has had an impact on their mentality, so that they are required to live a childfree lifestyle. This research is a type of normative research that looks at the symptoms that occur in the sandwich generation psychologically, so that the burden they experience causes them to choose to be childfree. The results of this research show that the sandwich generation psychologically often experiences two impacts; First, some of the sandwich generation experience mental disorders, so that in their households they choose to live a childfree lifestyle, because of the burden that weighs on them, so they think that children are a burden that will add to the burden in their lives. Second, some people think that the sandwiches that happen to their family tend to make them experienced in managing responsibilities, so that they actually have lots of offspring.